Apple Role through Fair Labour Association (FLA) in order to Fixing Foxconns Sweatshop in China - Sari, Sarah Puspa (Jurnal Ilmiah HUBUNGAN INTERNASIONAL, 2014)
In 2010, there is several news about suicides at Foxconns factory in ShenZhen, China, a plant that assembles iPhones, iPods, and iPads for Apple. In order to fix this sweatshop practice in its chain, Apple make affliliateswith independent labor monitoring organizations engaged by the Fair Labour Association (FLA) as participating company. In FLA charter stated that the member should adopted a "Workplace Code of Conduct". The FLA Workplace Code of Conduct defines labor standards that aim to achieve decent and humane working conditions. FLA conducts independent assesments of a random sample of companies supplier factories such as the three Foxconn facilities in Longhua, Guanlan and Chengdu to investigates the situation in Foxconn. Based on assessment, FLA founded that the condition in Foxconns factories, there is several violation on FLA Code Standard. FLA has made a series of recommendations to Apple and Foxconn, which is in immediate action required and sustainable remediation required. Thus, Apple released Supplier Responsibility Standards to make a standard for its own supply chain including Foxconn to meet several acquirements in order to prevent sweatshops practice.